Ventromedial prefrontal cortex activity and pathological worry in generalised anxiety disorder. (9th May 2018) - Via, E.; Fullana, M. A.; Goldberg, X.; Tinoco-González, D.; Martínez-Zalacaín, I.; Soriano-Mas, C.; Davey, C. G.; Menchón, J. M.; Straube, B.; Kircher, T.; Pujol, J.; Cardoner, N.; et al.
Abstract : Background: Pathological worry is a hallmark feature of generalised anxiety disorder (GAD), associated with dysfunctional emotional processing. The ventromedial prefrontal cortex (vmPFC) is involved in the regulation of such processes, but the link between vmPFC emotional responses and pathological v . adaptive worry has not yet been examined. Aims: To study the association between worry and vmPFC activity evoked by the processing of learned safety and threat signals. Method: In total, 27 unmedicated patients with GAD and 56 healthy controls (HC) underwent a differential fear conditioning paradigm during functional magnetic resonance imaging. Results: Compared to HC, the GAD group demonstrated reduced vmPFC activation to safety signals and no safety–threat processing differentiation. This response was positively correlated with worry severity in GAD, whereas the same variables showed a negative and weak correlation in HC. Conclusions: Poor vmPFC safety–threat differentiation might characterise GAD, and its distinctive association with GAD worries suggests a neural-based qualitative difference between healthy and pathological worries. Declaration of interest: None.